The influence of climate risk on interest spread in the banking sector performance in Kenya - Lucy Maru; Steve Anyona Makambi (Kenya Bankers Association (KBA), 2024)
One of the most important steps towards a greener economy is assessing the path through which climate risks are internalized in to bank portfolios. Aligned with literature on market risks and credit risks emanating from climate risk exposure, this paper sought to assess the feedback effect between banking sector performance and climate risk and identify the transmission pathway of climate risk to banking sector performance. The paper employed conditional process analysis. Using meteorological data, data on weather disasters, bank level data and interest rate between 2011- 2022, the study found that: - i) there exists a relationship between climate risk and bank performance to the extent that changes in interest rate spread are mediated by climate disasters having been moderated by temperature variation. ii) increase in non-performing loans leads to decrease in interest rate spread. Therefore, this paper persuades policy makers to adjust risks to include climate related risks and develop risk models that capture climate related risks in risk pricing. Additionally, the paper recommends that the regulator may develop an adaptable reporting framework to transition bank portfolios to a green and financially sustainable path.
Keywords: 330; Climate risk; Interest rate spread; non-performing loans; Carbon transition